Dietetic Students' Perceived Anxiety towards Simulation Activities: A Mixed-methods Pilot Study. - ROSA, MYLÈNE; BODNARUC, ALEXANDRA M.; GIROUX, ISABELLE (Canadian Journal of Dietetic Practice & Research, 2025)
Purpose: To assess dietetic students' anxiety levels before and after a series of simulations and to document students' perceived sources of anxiety while completing simulation-based learning activities. Methods: A mixed-method convergent pilot study was conducted. Students enrolled in a Nutrition Assessment course that included a series of four simulations were invited to participate. Students completed an online pre-post simulation survey and engaged in individual interviews and a focus group discussion. The questionnaires included demographic questions and the French State-Trait Anxiety Inventory. Nonparametric tests and thematic analysis were used to examine data. Results: Fourteen students participated in the study's quantitative component and seven in the qualitative component. There was a significant decrease in trait (44.5 ± 13.8 vs 32.0 ± 14.0, P = 0.01) and state (47.0 ± 11.2 vs 33.0 ± 18.0, P = 0.05) anxiety from pre- to postsimulations. Individual factors influencing students' anxiety levels were stress and self-confidence. External factors influencing students' anxiety levels were unknown situations, observers, patient profiles, observers' feedback, preparation level, and academic setting. Conclusions: Our findings suggest that ensuring the educator is not present during simulations, advance preparation, and reassurance that simulations are a learning and not an evaluation activity may be effective pedagogical strategies for dietetic educators to reduce learners' anxiety and facilitate competency development.